Spermidine attenuates bleomycin-induced lung fibrosis by inducing autophagy and inhibiting endoplasmic reticulum stress (ERS)-induced cell death in mice - Baek, Ae Rin; Hong, Jisu; Song, Ki Sung; Jang, An Soo; Kim, Do Jin; Chin, Su Sie; Park, Sung Woo (Experimental & molecular medicine, 2020)
Spermidine is an endogenous biological polyamine that plays various longevity-extending roles and exerts antioxidative, antiaging, and cell growth-promoting effects. We previously reported that spermidine levels were significantly reduced in idiopathic pulmonary fibrosis (IPF) of the lung. The present study assessed the potential beneficial effects of spermidine on lung fibrosis and investigated the possible mechanism. Lung fibrosis was established in mice using bleomycin (BLM), and exogenous spermidine was administered daily by intraperitoneal injection (50 mg/kg in phosphate-buffered saline). BLM-induced alveolar epithelial cells showed significant increases in apoptosis and endoplasmic reticulum stress (ERS)-related mediators, and spermidine attenuated BLM-induced apoptosis and activation of the ERS-related pathway. Senescence-associated β-gal staining and decreased expression of p16 and p21 showed that spermidine ameliorated BLM-induced premature cellular senescence. In addition, spermidine enhanced beclin-1-dependent autophagy and autophagy modulators in IPF fibroblasts and BLM-induced mouse lungs, in which inflammation and collagen deposition were significantly decreased. This beneficial effect was related to the antiapoptotic downregulation of the ERS pathway, antisenescence effects, and autophagy activation. Our findings suggest that spermidine could be a therapeutic agent for IPF treatment. Lung fibrosis: Spermidine, anti-aging compound inhibit lung fibrosis in mice A natural widely occurring molecule with anti-aging properties may offer a new therapeutic option for patients with idiopathic pulmonary fibrosis(IPF). Sung Woo Park and colleagues from Soonchunhyang University Bucheon Hospital, South Korea, administered the anti-aging compound spermidine to mice with bleomycin-induced lung fibrosis. The team had previously shown that IPF lung express lower levels of spermidine than do healthy individuals. In the current investigations, the researchers demonstrated that treatment of spermidine attenuate inflammation and reduce collagen deposition in mouse lungs. On a molecular level, spermidine limited oxidative stress induced cell death and growth arrest by preventing the build-up of misfolded proteins and by activating pathways for the removal of dysfunctional components from the cell.